A crown so silver - Selene, Lyra (Selene, Lyra. Fair Folk, 2025)
"After her sacrifice on the Ember Moon, Fia is flush with powerful magic and eager to rush into battle against her murderous sister, Eala. However, Fia's new husband Irian suggests a retreat to the Silver Isle, a snowy island at the edge of the fae world, ruled by a wily smith-king. The Silver Isle proves far from a safe haven, as Fia and Irian become embroiled in the Tournament of Kings competing for a magical forging of the winner's choosing-against Eala. Fia and Irian's new relationship is put to the test as they navigate their conflicting motivations, shifting allegiances, and ancient magic. With the end of the tournament looming and Eala's threat growing, Fia must decide just how much she's willing to sacrifice to defeat her sister"--